The effects of altered cycling posture and cadence on subsequent running mechanics - Durham, R. D.; Abendroth-Smith, J. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Many triathletes complain of experiencing difficulties while running following cycling, but these difficulties are usually only felt in about the first kilometer of the run (Millet and Vleck, 2000). To improve performance in the run portion of a triathlon, it would be beneficial to minimize the negative effects from cycling. The purpose of this study was to compare the effects of two cycling positions, sitting up and spinning at the end of the cycling portion versus staying in the tucked riding position, on subsequent running mechanics.